2021
DOI: 10.1039/d1ra07317f
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of heparin-binding EGF-like growth factor activity on heparin-modified poly(N-isopropylacrylamide)-grafted surfaces

Abstract: Activity of HB-EGF bound to a heparin-modified poly(N-isopropylacrylamide) (PIPAAm)-grafted surface was preserved through specific binding to heparin, whereas physisorbed HB-EGF on a PIPAAm-grafted surface greatly diminished its activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Previous studies have reported that physisorbed heparin‐binding proteins such as bFGF and HB‐EGF on PIPAAm‐grafted surfaces impair their activity. [ 32,33 ] In Figure 6B, IC1 and PIPAAm surfaces showed the same level of bFGF binding as IC1‐hep surface, indicating that nonspecific physisorption on these surfaces was considerable. In contrast, the bFGF‐bound IC1‐ap‐hep surface prepared using CuAAC held more active bFGF (Figure 6B) and exhibited greater ECFC proliferation (Figure 6C) than the IC1‐hep surface prepared by condensation.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported that physisorbed heparin‐binding proteins such as bFGF and HB‐EGF on PIPAAm‐grafted surfaces impair their activity. [ 32,33 ] In Figure 6B, IC1 and PIPAAm surfaces showed the same level of bFGF binding as IC1‐hep surface, indicating that nonspecific physisorption on these surfaces was considerable. In contrast, the bFGF‐bound IC1‐ap‐hep surface prepared using CuAAC held more active bFGF (Figure 6B) and exhibited greater ECFC proliferation (Figure 6C) than the IC1‐hep surface prepared by condensation.…”
Section: Discussionmentioning
confidence: 93%
“…Bone morphogenetic protein 2 was coupled to poly(glycidyl methacrylate) and poly(oligoetheyleneglycolmethacrylate) brushes, to promote osteo-differentiation and bone regeneration [59,60]. Heparin was also coupled to grafted copolymers of poly(N-isopropylacrylamide-co-2-carboxyisopropylacrylamide), to enable the capture of basic fibroblast growth factor and heparin binding growth factor, for the culture of hepatocytes and hepatocyte sheets [61,62]. Finally, sulfonated brushes such as poly(styrene sulfonate) and sulfonated poly(3-O-methacryloyl-1,2:5,6-di-O-isopropylidene-Dglucofuranose) have also been proposed for the capture of monocyte chemoattractant protein-1 and the inhibition of coagulation [63,64].…”
Section: Introductionmentioning
confidence: 99%
“…61,62 Heparin was also coupled to grafted copolymers of poly(N-isopropylacrylamide-co-2-carboxyisopropylacrylamide), to enable the capture of the basic fibroblast growth factor and heparin binding growth factor, for the culture of hepatocytes and hepatocyte sheets. 63,64 Finally, sulfonated brushes such as PSS and sulfonated poly(3-Omethacryloyl-1,2:5,6-di-O-isopropylidene-D-glucofuranose) have also been proposed for the capture of monocyte chemoattractant protein-1 and the inhibition of coagulation. 65,66 Despite their capacity to mimic the sulfate chemistry of heparin, sulfonated polymer brushes such as PSS and poly(sulfopropyl methacrylate) (PSPMA) have not been explored for the direct capture of BMPs and other growth factors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…TGF-β was coupled to poly(ethylene glycol) brushes decorating microparticles through azide-mediated Staudinger ligation, using a grafting to approach, to modulate T-cell activation . BMP2 was coupled to poly(glycidyl methacrylate) and poly(oligoethylene glycolmethacrylate) brushes, to promote osteodifferentiation and bone regeneration. , Heparin was also coupled to grafted copolymers of poly( N -isopropylacrylamide- co -2-carboxyisopropylacrylamide), to enable the capture of the basic fibroblast growth factor and heparin binding growth factor, for the culture of hepatocytes and hepatocyte sheets. , Finally, sulfonated brushes such as PSS and sulfonated poly(3- O -methacryloyl-1,2:5,6-di- O -isopropylidene- d -glucofuranose) have also been proposed for the capture of monocyte chemoattractant protein-1 and the inhibition of coagulation. , …”
Section: Introductionmentioning
confidence: 99%